Digital synthetic polymers for information storage. (14th February 2023) - Yu, Li; Chen, Baiyang; Li, Ziying; Huang, Qijing; He, Kaiyuan; Su, Yue; Han, Zeguang; Zhou, Yongfeng; Zhu, Xinyuan; Yan, Deyue; Dong, Ruijiao
Abstract : This tutorial review summarizes recent advances in salient features of digital synthetic polymers for data storage, including encoding, decoding, editing, erasing, encrypting, and repairing. Abstract : Digital synthetic polymers with uniform chain lengths and defined monomer sequences have recently become intriguing alternatives to traditional silicon-based information devices or natural biomacromolecules for data storage. The structural diversity of information-containing macromolecules endows the digital synthetic polymers with higher stability and storage density but less occupied space. Through subtly designing each unit of coded structure, the information can be readily encoded into digital synthetic polymers in a more economical scheme and more decodable, opening up new avenues for molecular digital data storage with high-level security. This tutorial review summarizes recent advances in salient features of digital synthetic polymers for data storage, including encoding, decoding, editing, erasing, encrypting, and repairing. The current challenges and outlook are finally discussed to offer potential solution guidance and new perspectives for the creation of next-generation digital synthetic polymers and broaden the scope of their applicability.